Supporting Safer Spaces: How School Administrators Shape the School Culture for Sexual and Gender Minority Students - Ariadne Jevnikar (Canadian Journal for New Scholars in Education, 2022)
This review highlights gaps in existing literature concerning how sexual and gender minority (SGM) students can be best supported at school, as influenced by school administration. SGM students experience additional challenges to their gender normative, heterosexual peers that affect their physical, mental, and social well-being. Student groups which support SGM youth such as Gay-Straight or Gender-Sexuality Alliances (GSAs) have a positive impact on students’ sense of belonging and a school’s overall climate compared to schools without similar groups. School climate is also influenced by school leaders through policy interpretation, resource allocation, and their individual leadership practices. Research shows that support from school administrators for SGM students is crucial for teachers to initiate more inclusion of this at-risk group. Existing research does not provide sufficient insight into the complex task of leading a school while fostering a sense of belonging for SGM students; my research aims to fill this gap.